Mental health professionals’ perceived barriers and enablers to shared decision-making in risk assessment and risk management: a qualitative systematic review - Nafiso Ahmed (BMC, 2021)
Abstract Background Risk assessment and risk management are fundamental processes in the delivery of safe and effective mental health care, yet studies have shown that service users are often not directly involved or are unaware that an assessment has taken place. Shared decision-making in mental health systems is supported by research and advocated in policy. This systematic review (PROSPERO: CRD42016050457) aimed to explore the perceived barriers and enablers to implementing shared decision-making in risk assessment and risk management from mental health professionals’ perspectives. Methods PRISMA guidelines were followed in the conduct and reporting of this review. Medline, CINAHL, EMBASE, PsycINFO, AMED and Internurse were systematically searched from inception to December 2019. Data were mapped directly into the Theoretical Domains Framework (TDF), a psychological framework that includes 14 domains relevant to behaviour change. Thematic synthesis was used to identify potential barriers and enablers within each domain. Data were then matched to the three components of the COM-B model: Capability, Opportunity, and Motivation. Results Twenty studies met the eligibility criteria. The findings of this review indicate that shared decision-making is not a concept commonly used in mental health services when exploring processes of risk assessment and risk management. The key barriers identified were ‘power and best interest’ (social influences) and ‘my professional role and responsibility’ (social/professional role and identity). Key enablers were ‘therapeutic relationship’ (social influences) and ‘value collaboration’ (reinforcement). The salient barriers, enablers and linked TDF domains matched COM-B components ‘opportunity’ and ‘motivation’. Conclusion The review highlights the need for further empirical research to better understand current practice and mental health professionals’ experiences and attitudes towards shared decision-making in risk assessment and risk management.